Enhanced gases separation of cellulose acetate membrane using N-Methyl-1-2 pyrrolidone as fabrication solvent - Mubashir, M. (Universiti Malaysia Pahang, 2018)
Among the various polyimides, cellulose acetate (CA) as the membrane material in the market of gases separation processes is extensively used. However, CA membrane demonstrates relatively low CO2 permeability and low CO2/N2 and CO2/CH4 gas pair selectivity. Besides, fabrication of defect-free CA membrane challenging, and fabrication solvent control the non-selective voids of the membrane. Although, there were few studies reported on the development of CA membrane using various solvents; the fabrication of CA membrane using methyl-2-pyrrolidone (NMP) is scarcely reported in the literature and detailed investigation is needed. Thus, the objective of the present work is to fabricate CA membrane using NMP solvent. Analytical tools have verified the structure, morphology and bond vibration of the resultant membrane, respectively. The resultant CA membrane showed the CO2 permeability, CO2/CH4 and CO2/N2 ideal selectivity of 15.56 Barrer, 10.71 and 8.80, respectively. The performance of the resultant membrane was found higher the previously reported studies for CA membrane fabricated using different solvents. Thus, it can be concluded that the NMP is effective solvent and it can be recommended to use a solvent for fabrication of other types of membranes. Â© Universiti Malaysia Pahang, Malaysia.